Analysis of the Bearing Capacity of Pile Foundations with the Meyerhoff Method in the New Terminal Building at Haji Hasan Aroeboesman Ende Airport - Kwico Yusan Ladisma, Feyza; Winiasri, Linda; Meilawati Eka Putri, Karina (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
Pile foundation is a type of foundation that has the function of transmitting structural loads to the soil layer, with high bearing capacity at a certain depth. The purpose of this analysis is to calculate the bearing capacity of single pile, the bearing capacity of pile group and to calculate settlement of single pile and pile group from Sondir and Standard Penetration Test (SPT). In this calculation the Meyerhoff method is used. The new terminal construction project at Haji Hasan Aroeboesman Ende Airport uses pile foundations. The location of the new terminal building is located at the coordinates of 8°50'51" S 121°39'54" E, the location is quite close to the beach with sandy soil types, a pile foundation is suitable for use. Based on acquired sondir and SPT data, foundation bearing capacity at two test points, Qult sondir data: 404,637 tons and 412,177 tons. SPT data obtained by Qult: 887,112 tons and 928,158 tons. The results of the bearing capacity of group 4 piles on the survey data: 338,120 tons and 342,300 tons. While SPT data: 983,630 tons and 1,029,142 tons. The results of the group 3 data group capacity survey: 253,590 tons and 256,725 tons. While SPT data: 737,723 tons and 772,069 tons. Results of data group capacity survey from group 2: 240,221 tons and 243,191 tons. While SPT data: 698,831 tons and 713,363 tons. Calculation results of single settlement and pile group 4: 20,439mm and 90,749mm. Calculation results of single settlement and pile group 3: 27.123mm and 120,428mm. Calculation results of single settlement and pile group 2: 40,297mm and 179,920mm. In this computational analysis, the bearing capacity of single pile and group pile is declared safe and meets the requirements of standard SNI 8460: 2017 from the results of the specified calculation should not exceed 190 mm